ANGKA KEJADIAN FISTULA PALATUM PADA PASIEN POST-PALATOPLASTY DI RS AWAL BROS SUDIRMAN PEKANBARU PERIODE JANUARI 2011-DESEMBER 2013 - Atthahirah, Amelia Intan; Pamungkas, Kuswan Ambar; nMursali, Laode Burhauddin (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
Cleft palate is the most common craniofacial abnormality encountered by plastic surgeons. Definitive therapy for cleft palate is throughout a palatoplasty operation. The most common complication of palatolasty is the formation of palatal fistula. The goal of this study is to determine the incidence of palatal fistula in postpalatoplasty patients at Awal Bros Hospital Sudirman Pekanbaru period January 2011-Desember 2013. This study is a descriptive retrospective study with a cross-sectional approach. Sample of this study includes all medical records that fulfill the inclusion criteria. 29 medical records are included as samples in this study. The results of this study suggests that 1 out of 29 patients has palatal fistula (3,4%). Patient with palatal fistula is in the group age >18bulan and is a male. Patient is diagnosed with complete unilateral dextra cleft palate.Keyword: palatal fistula, age, sex, diagnose.